ANALISIS PENGARUH CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBERADAAN KOMITE MANAJEMEN RISIKO (Studi kasus pada perusahaan yang Listing di BEI periode 2008-2010) - Tri Wahyuni; Puji Harto (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the influence of  corporate governance and firm characteristics to existence of Risk Management Committee (RMC) and type of RMC, whether it is  separated and combined with audit committee. Variables are  break down into independent commissioner, meeting frequencies, ownership type, auditor reputation, size of subsidiares, market risk, leverage, age, and company size. This study replicated prior study conducted by Subramaniam, et al. (2009) with some modification and elimination of variables. The statistic method to test the hypotheses is logistic regression analysis. Sample are collected using random sampling included in eighty non-bank companies listed in BEI for 2008-2010. This study used agency theory, corporate legitimacy, and signal theory to explain lingkage between variables. This study showed that some independent variables have positive effect to the existence of RMC namely meeting frequencies, size of subsidiares, and company size. While, independent variables that positively influence the existence of  Separate RMC were meeting frequencies and company size.